Media-based instructional innovations: opportunities, practices and challenges at Hossana College of Teacher Education. - Ergogo, Abayneh (Cogent Arts & Humanities, 2025)
The frequently used phrase 'the medium is the message' in teacher education refers to both successful teacher preparation and the creation of a common language for teaching. For the purpose of analyzing opportunities, practices and challenges related to media-based instructional innovations at Hossana College of Teacher Education, 42 teacher educators using availability sampling and 278 third-year pre-service teachers (145 linear and 133 specialists) using stratified random sampling were selected. We used five-point Likert-type items, open-ended questions and unstructured interviews. In addition to the descriptive analysis, the Mann–Whitney test and Pearson correlation methods were used. The findings demonstrated that, except a few concerns rose by college administrators, there are not enough opportunities and then there are persisting challenges related with the relevant stakeholders for the practice of media-based instructional innovations. Suggestions for the college to create and execute a better organized system of instructional media were also provided.